2017
DOI: 10.3390/w9010024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposed Artificial Substrate on the Competition between Phytoplankton and Benthic Algae: Implications for Shallow Lake Restoration

Abstract: Phytoplankton and benthic algae coexist in shallow lakes and the outcome of the competition between these two photoautotrophs can markedly influence water clarity. It is well established that exposed artificial substrate in eutrophic waters can remove nutrients and fine particles from the water column via the attached periphyton canopy. However, the effects of the introduction of artificial substrate on the competition between planktonic and benthic primary producers remain to be elucidated. We conducted a sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
(58 reference statements)
0
6
0
1
Order By: Relevance
“…How artificial substrate affects the competition between planktonic and benthic primary producers is not well-studied. A short-term outdoor mesocosm experiment was conducted [29] to test the hypothesis that the nutrient and light changes induced by exposed artificial substrate (polythene nets) would benefit the benthic algae and thus indirectly water clarity. It was found that the artificial substrate significantly reduced total nitrogen and phosphorus and phytoplankton biomass, while benthic algae biomass and water clarity increased.…”
Section: Mediterranean and Subtropical Climate Zonementioning
confidence: 99%
“…How artificial substrate affects the competition between planktonic and benthic primary producers is not well-studied. A short-term outdoor mesocosm experiment was conducted [29] to test the hypothesis that the nutrient and light changes induced by exposed artificial substrate (polythene nets) would benefit the benthic algae and thus indirectly water clarity. It was found that the artificial substrate significantly reduced total nitrogen and phosphorus and phytoplankton biomass, while benthic algae biomass and water clarity increased.…”
Section: Mediterranean and Subtropical Climate Zonementioning
confidence: 99%
“…Comprehensively, taking in to consideration the cost performance and construction convenience, the AAP was a more favorable material, with longevity over 15 years, for the application in the ecological restoration of shallow eutrophic waters. Due to the structure of plentiful micropores between the microfibers (8.5-9.0 cm per microfiber), the periphyton is provided with adhesive surfaces of 8000 m 2 /m 3 , and results in strong adsorption and absorption.Research concerning periphyton has predominantly focused upon the purifying capacity of periphyton in bioreactors and rivers [23,24], while studies in eutrophic lakes remain rare [25,26]. Taking the periphyton biofilm as an assemblage, there is a need to understand the performance and processes involved with algal-bacterial biofilm-based wastewater treatment projects.…”
mentioning
confidence: 99%
“…Research concerning periphyton has predominantly focused upon the purifying capacity of periphyton in bioreactors and rivers [23,24], while studies in eutrophic lakes remain rare [25,26]. Taking the periphyton biofilm as an assemblage, there is a need to understand the performance and processes involved with algal-bacterial biofilm-based wastewater treatment projects.…”
mentioning
confidence: 99%
“…Stabilizing the bank line, altering the slope and hydrology, manipulating the flow regime and dredging the sediment are usually employed in the implementations of these projects [14,18,43]. More recently, a focus on water quality improvement have driven many FER implementations, in which an array of in-situ physicochemical and biological techniques has been developed and applied with an attempt to remove or stabilize pollutants and nutrients in water column or sediment [8,25,35]. Among these techniques, revegetation has gained considerable attention.…”
Section: S Environmental Communiqués Issued By the Ministry Of Ementioning
confidence: 99%